Safety and benefits of antenatal oral iron supplementation in low‐income countries: a review. (8th March 2017) - Mwangi, Martin N.; Prentice, Andrew M.; Verhoef, Hans
Summary: The World Health Organization recommends universal iron supplementation of 30–60 mg/day in pregnancy but coverage is low in most countries. Its efficacy is uncertain, however, and there has been a vigorous debate in the last decade about its safety, particularly in areas with a high burden of malaria and other infectious diseases. We reviewed the evidence on the safety and efficacy of antenatal iron supplementation in low‐income countries. We found no evidence that daily supplementation at a dose of 60 mg leads to increased maternal Plasmodium infection risk. On the other hand, recent meta‐analyses found that antenatal iron supplementation provides benefits for maternal health (severe anaemia at postpartum, blood transfusion). For neonates, there was a reduced prematurity risk, and only a small or no effect on birth weight. A recent trial showed, however, that benefits of antenatal iron supplementation on maternal and neonatal health vary by maternal iron status, with substantial benefits in iron‐deficient women. The benefits of universal iron supplementation are likely to vary with the prevalence of iron deficiency. As a consequence, the balance between benefits and risks is probably more favourable in low‐income countries than in high‐income countries despite the higher exposure to infectious pathogens.